2022
DOI: 10.1097/dcr.0000000000002082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Curettage Plus Platelet-Rich Plasma Gel and Curettage Plus Phenol Application in Treatment of Pilonidal Sinus Disease: A Randomized Trial

Abstract: BACKGROUND:As a chronic condition, pilonidal disease affects a young population, and recovery after the surgical procedures performed to treat this condition require time off from work. Therefore, the search for an ideal treatment is still ongoing. OBJECTIVE:The aim of this study was to compare early and late results of 2 minimally invasive treatment options used to treat pilonidal disease.DESIGN: This study was designed as a parallel group randomized clinical trial. SETTINGS:This study took place at an outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…A total of 37 studies were identified and nine met the inclusion criteria (Tables 2 & 3); the included studies originated from Greece [26], Iran [27–29], Russia [30], Egypt [31] and Turkey [32–34] and were conducted between 2009 and 2021. Eight included studies were RCT's [26–33], and one was a case control study by Kurt et al [34], and all studies compared PRP treated wounds to dressings alone (Tables 2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 37 studies were identified and nine met the inclusion criteria (Tables 2 & 3); the included studies originated from Greece [26], Iran [27–29], Russia [30], Egypt [31] and Turkey [32–34] and were conducted between 2009 and 2021. Eight included studies were RCT's [26–33], and one was a case control study by Kurt et al [34], and all studies compared PRP treated wounds to dressings alone (Tables 2, 3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 37 studies were identified and nine met the inclusion criteria (Tables 2 & 3); the included studies originated from Greece [26], Iran [27][28][29], Russia [30], Egypt [31] and Turkey [32][33][34] and were conducted between 2009 and 2021. Eight included studies were RCT's [26][27][28][29][30][31][32][33], and one was a case control study by Kurt et al [34], and all studies compared PRP treated wounds to dressings alone (Tables 2, 3). Five studies applied PRP solution to wounds on multiple days post-operatively [26,28,[30][31][32], while the other four studies all applied it within the first 36 h [27,29,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Leider fehlen immer noch die randomisierten Studien, die verschiedene minimalinvasive Verfahren untereinander vergleichen, obwohl solche Studien vom Design her wirklich einfach durchzuführen wären. Die einzige solche Studie wurde von Sevinc et al durchgeführt und verglich die Phenolbehandlung mit Platelet-rich Plasma (PRP), das in den kürettierten Sinus eingeführt wurde [17]. Es konnte eine Heilungsrate (Cave: ein anderer Endpunkt!)…”
Section: Alternativenunclassified
“…2,4 The flap procedures flatten the contour of the buttocks and neutralize the impact of these 2 factors. 5,6 However, the buttock-contour flattening is cosmetically inferior, irreversible, and not preferred by the patients. 7 In laying-open (unroofing) curettage, these 2 modifiable factors are not neutralized, and it is pertinent to instruct the patients to take care of these 2 risk factors postoperatively to avoid recurrence (by regularly cleaning hairs and applying talcum powder to the gluteal cleft to keep it dry).…”
Section: To the Editor—mentioning
confidence: 99%